The Death Penalty In The Draft Criminal Code (RKUHP): What Are The Regulations And Mechanisms? - Matrutty, Ruth Gracia Imanuela; Saimima, Judy Marria (JURNAL LEGALITAS, 2023)
This article examines the death penalty provisions in the Draft Criminal Code (RKUHP), focusing on its regulation and application mechanisms. Using a normative juridical approach, the study provides a detailed analysis of the draft's stance on the death penalty. The RKUHP treats the death penalty as a special punishment, which can be alternatively imposed with life imprisonment or a maximum of 20 years in prison for crimes outlined in the Criminal Code and other specific laws. The research identifies a key issue: while the RKUHP aims to achieve various goals through punishment, the death penalty fails to meet some of these objectives, such as the social rehabilitation of convicts and the resolution of conflicts arising from criminal acts. The study suggests that imprisonment as an alternative to the death penalty has negative effects on convicts and proposes exploring other punitive alternatives. These alternatives should align with the goals of justice and rehabilitation outlined in the criminal law, offering solutions that do not harm the convict's prospects. This research highlights the need for a more effective and humane approach to punishment in the criminal justice system.